Grasping the 'teachable moment': time since diagnosis, symptom burden and health behaviors in breast, colorectal and prostate cancer survivors - Bluethmann, Shirley M.; Basen-Engquist, Karen; Vernon, Sally W.; Cox, Matthew; Gabriel, Kelley Pettee; Stansberry, Sandra A.; Carmack, Cindy L.; Blalock, Janice A.; Demark-Wahnefried, Wendy (Psycho-oncology (Chichester, England), 2015)
Background A cancer diagnosis may provide a ‘teachable moment’ in cancer recovery. To better understand factors influencing lifestyle choices following diagnosis, we examined associations between time since diagnosis and symptom burden with recommended dietary (e.g., five or more fruit/vegetable servings/day), physical activity (e.g., >150 active min, 3–5 times/week), and smoking behaviors (i.e., eliminate tobacco use) in cancer survivors. Methods We analyzed cross‐sectional survey data collected from breast (n = 528), colorectal (n = 106), and prostate (n = 419) cancer survivors following active treatment at The University of Texas MD Anderson Cancer Center. Four regression models were tested for behaviors of interest. Additionally, we assessed symptom burden as a potential moderator and/or mediator between time since diagnosis and behaviors. Results Respondents were mostly female (55%) and non‐Hispanic White (68%) with a mean age of 62.8 ± 11.4 years and mean time since diagnosis of 4.6 ± 3.1 years. In regression models, greater time since diagnosis predicted lower fruit and vegetable consumption (B = −0.05, p = 0.02) and more cigarette smoking (B = 0.06, p = 0.105). Greater symptom burden was a significant negative predictor for physical activity (B = −0.08, p < .001). We did not find evidence that symptom burden moderated or mediated the association between time since diagnosis and health behaviors. Conclusion We assessed the prevalence of recommended behaviors in the context of other challenges that survivors face, including time since diagnosis and symptom burden. Our results provide indirect evidence that proximity to a cancer diagnosis may provide a teachable moment to improve dietary and smoking behaviors and that symptom burden may impede physical activity following diagnosis. Copyright © 2015 John Wiley & Sons, Ltd.